Environmental protection clothing design and materials based on green design concept - Yang, Cuiyu; Zhang, Xianglei (Frontiers in Materials, 2023)
To maintain high-quality and aesthetically pleasing interior clothing design, the use of eco-friendly materials is imperative. Texture, a fundamental element in images, reveals surface characteristics and aids in visual interpretation. This paper, rooted in the green design concept, explores the integration of eco-friendly materials in clothing design. It introduces an enhanced DCNN-based algorithm for extracting texture features from clothing materials and examines how eco-friendly materials are visually represented in clothing design. The paper addresses the limitation of moment invariants by combining them with boundary direction characteristics, enhancing the algorithm's ability to capture shape and spatial distribution information across the entire image.Experimental results validate the algorithm's effectiveness in image analysis and the extraction of apparel material texture features. This study offers a novel perspective on sustainable clothing design by applying environmental design principles to the apparel design domain.